2008
DOI: 10.1093/toxsci/kfn031
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Dichloropropionanilide (DCPA) Inhibits T-Cell Activation by Altering the Intracellular Calcium Concentration following Store Depletion

Abstract: Stimulation of T cells through the T-cell receptor results in the activation of a series of signaling pathways that leads to the secretion of interleukin (IL)-2 and cell proliferation. Influx of calcium (Ca(2+)) from the extracellular environment, following internal Ca(2+) store depletion, provides the elevated and sustained intracellular calcium concentration ([Ca(2+)](i)) critical for optimal T-cell activation. Our laboratory has documented that exposure to the herbicide 3,4-dichloropropionanilide (DCPA) inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Previously we showed that the haloanilide DCPA blocks store‐operated Ca 2+ channel function in Jurkat cells with no effect on ER Ca 2+ content (Lewis et al, 2008). DCPA also reduced SOCe in osteoclasts by 27.5% (n = 3; data not shown).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously we showed that the haloanilide DCPA blocks store‐operated Ca 2+ channel function in Jurkat cells with no effect on ER Ca 2+ content (Lewis et al, 2008). DCPA also reduced SOCe in osteoclasts by 27.5% (n = 3; data not shown).…”
Section: Resultsmentioning
confidence: 98%
“…We further establish that DCPA‐mediated CRAC channel inhibition occurs via inhibition of STIM1–Orai1 interaction. DCPA is a haloanilide compound with relatively low systemic toxicity that can inhibit Ca 2+ influx in macrophages and T cells as well as having potent anti‐inflammatory activity (Xie et al, 1997; Ustyugova et al, 2007; Lewis et al, 2008). As such, our findings may have significant therapeutic implications.…”
mentioning
confidence: 99%
“…2007, 2008). Influx of Ca 2+ from the extracellular environment, following internal Ca 2+ store depletion, provides the elevated and sustained [Ca 2+ ] i levels, which is associated with the activation of the CRAC channels on the plasma membrane (Prakriya and Lewis 2001; Lewis et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, extracellular Ca 2+ influx is essential [22]. The depletion of intracellular Ca 2+ stores activates STIM/Orai [21,23] and CRAC [11,24] channels, resulting in an influx that sustains the newly elevated Ca 2+ levels.…”
Section: Introductionmentioning
confidence: 99%